Dendritic mesoporous silica supported catalyst as well as preparation method and application thereof

By using dendritic mesoporous silica-supported catalysts and supporting Zn and Zr metals in the ethanol-to-butadiene reaction, the problems of catalyst active components are solved, high conversion, selectivity and reaction stability are achieved, and the industrial application of ethanol-to-butadiene technology is supported.

CN119588332APending Publication Date: 2025-03-11DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411781762.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing ethanol-making butadiene technology has problems with agglomeration and deactivation of catalyst active components, resulting in low conversion and selectivity and poor reaction stability.

Method used

Using dendritic mesoporous silica-supported catalyst, dendritic mesoporous silica nanospheres with unique central radial pore structures are prepared in a water/oil biphasic system and loaded with dehydrogenated metals Zn and transition metals Zr, inhibiting the agglomeration and carbon accumulation of the active components.

Benefits of technology

The high stability of ethanol is achieved in one step, butadiene is produced with high conversion and selectivity, and good reaction stability is maintained under different operating conditions, extending the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588332A_ABST
    Figure CN119588332A_ABST
Patent Text Reader

Abstract

The invention discloses a dendritic mesoporous silica supported catalyst as well as a preparation method and application thereof. The catalyst comprises a dendritic mesoporous silica carrier and transition metal supported on the dendritic mesoporous silica carrier, the transition metal is Zn and Zr. The transition metal-loaded dendritic mesoporous silica catalyst is synthesized for the first time, dendritic mesoporous silica with a unique central radial pore structure is selected as a carrier and has a dendritic cavity structure, and transition metals Zn and Zr are further loaded on the dendritic mesoporous silica, so that the transition metal-loaded dendritic mesoporous silica catalyst is prepared. The high load of the transition metal is realized; meanwhile, the preparation process is simple and easy to industrialize, has a relatively good application prospect in a reaction for preparing butadiene from ethanol, can realize high-activity, high-selectivity and high-stability generation of the target product butadiene from ethanol, and has the remarkable advantages of low cost, easiness in preparation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparing butadiene from ethanol, and more specifically to a dendritic mesoporous silica-supported catalyst and a preparation method and application thereof. Background Art

[0002] Butadiene, as a key cornerstone in the chemical industry chain, is widely used in the production of synthetic rubber, synthetic resin and other materials. It is an important raw material supporting the vigorous development of many industries such as automobile manufacturing and medical health (Tong Liu, Liu Zongzhang, Zhang Minhua. Research progress in the preparation of 1,3-butadiene by ethanol [J]. Chemical Industry and Engineering, 2012, 29 (04): 38-44.). At present, butadiene is mainly obtained by extracting C4 by-products in the process of naphtha cracking ethylene. This traditional production method is highly dependent on non-renewable petroleum resources and faces the dual challenges of resource depletion and environmental pressure (Makshina, EV; Dusselier, M.; Janssens, W.; Degreve, J.; Jacobs, PA; Sels, BF, Review of old chemistry and new catalytic advances in the on-purpose synthesis of butadiene. Chem. Soc. Rev., 2014, 43, 7917-7953.).

[0003] In this context, ethanol-to-butadiene technology stands out with its unique environmental protection and sustainability advantages and has become the focus of industry attention. As a renewable resource, the process of converting ethanol into butadiene not only reduces dependence on petrochemical resources, but also conforms to the development trend of global green chemistry and circular economy, showing broad prospects for industrial application (Pomalaza G, Arango Ponton P, Capron M, Dumeignil F. Ethanol-to-butadiene: the action and its catalysts. Catalysis Science & Technology. 2020; 10(15): 4860-911.).

[0004] The process of producing butadiene from ethanol is relatively complicated, involving multiple consecutive reaction steps such as ethanol dehydrogenation, aldol condensation, dehydration and MPVO reduction, and the catalytic system is relatively complex. In this technical path, the one-step method and the two-step method have their own advantages. Compared with the two-step method, the one-step method can achieve a higher conversion rate and lower energy consumption, but it is more prone to deactivation due to the agglomeration and carbon deposition of the dehydrogenation center. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned defects of the prior art and provide a dendritic mesoporous silica-loaded catalyst and a preparation method and application thereof. By synthesizing mesoporous SiO2 nanospheres with an ultra-large specific surface area, dehydrogenation metal Zn and transition metal Zr are loaded to inhibit the agglomeration and deactivation of active components. Its high mesoporous specific surface area and unique dendritic cavity structure can also effectively prevent carbon deposition, achieve high-stability one-step production of butadiene from ethanol, and achieve high conversion rate and selectivity, and have good reaction stability under different working conditions.

[0006] To achieve the above object, the technical solution of the present invention is as follows:

[0007] A dendritic mesoporous silica supported catalyst comprises a dendritic mesoporous silica support and a transition metal supported on the dendritic mesoporous silica support; the transition metal is Zn and Zr.

[0008] Optionally, in the catalyst, the mass of Zn accounts for 0.5wt% to 20wt% of the total mass of the catalyst, and the mass of Zr accounts for 1wt% to 25wt% of the total mass of the catalyst.

[0009] Optionally, the dendritic mesoporous silica carrier is a mesoporous SiO2 nanosphere with a dendritic skeleton structure, the diameter of the dendritic structure is 4nm to 10nm, the diameter of the SiO2 nanosphere is 20nm to 200nm, the pore size of the mesopore is 2nm to 30nm, and the specific surface area is 400m 2 / g~700m 2 / g.

[0010] The present invention also discloses a method for preparing the above-mentioned dendritic mesoporous silica-supported catalyst, comprising the following steps: co-impregnating a soluble salt solution of a transition metal into a dendritic mesoporous silica carrier, drying at 60°C to 200°C, and calcining in an air atmosphere at a calcination temperature of 350°C to 750°C for a calcination time of 2h to 8h to obtain the dendritic mesoporous silica-supported catalyst.

[0011] Optionally, the calcination temperature is 500° C. to 700° C., and the calcination time is 2 h to 6 h.

[0012] Optionally, the soluble salt of Zn in the soluble salt of transition metal includes at least one of zinc nitrate, zinc chloride and zinc acetate.

[0013] Optionally, the soluble salt of Zr in the soluble salt of the transition metal includes at least one of zirconium nitrate, zirconium oxynitrate and zirconium chloride.

[0014] Optionally, the method for preparing the dendritic mesoporous silica carrier comprises the following steps:

[0015] (1) adding a template to water and mixing to form a solution with a mass fraction of 5% to 35%, and then adding a catalyst and mixing to obtain an aqueous phase;

[0016] (2) mixing the silicon source and the solvent to form an oil phase with a volume fraction of 5% to 40%;

[0017] (3) stirring the oil phase and the water phase at 60°C to 90°C for 8h to 20h, removing the upper oil phase, and then heating to 80°C to 110°C and stirring and aging for 2h to 4h. After the reaction is completed, centrifugally washing and drying are performed, and then calcining at 300°C to 800°C in an air atmosphere for 1h to 8h to obtain the dendritic mesoporous silica carrier.

[0018] Optionally, in step (1), the mixing temperature is 45°C to 80°C, and the mixing time is 0.5h to 2h; the mass ratio of the template agent to the catalyst is 1:(100-500); the template agent is hexadecyltrimethylammonium chloride; and the catalyst is triethanolamine.

[0019] Optionally, in step (2), the molar ratio of the silicon source to the template is (0.5-1.5):1; the silicon source is tetraethyl orthosilicate; and the solvent is cyclohexane.

[0020] Optionally, in step (3), the drying temperature is 60°C to 120°C; the roasting temperature is 400°C to 600°C, and the roasting time is 2h to 6h.

[0021] Specifically, the present invention first prepares dendritic mesoporous silica with a unique central radial pore structure in a water / oil two-phase system, and rationally optimizes the preparation conditions to regulate the structure of the mesoporous silica nanomaterial, including particle size, pore size, specific surface area, etc., which is conducive to forming a mesoporous structure with a relatively good pore size distribution rate.

[0022] Optionally, the present invention has no special limitation on the mixing method, as long as the raw materials can be mixed evenly.

[0023] The invention also discloses an application of the dendritic mesoporous silica-supported catalyst in the reaction of preparing butadiene from ethanol.

[0024] Optionally, the application includes: the reaction is carried out in a fixed bed reactor at atmospheric pressure, with a reaction space velocity of 0.12h -1 ~10h -1 , using inert gas as carrier gas, the carrier gas space velocity is 500h -1 ~10000h -1 , the reaction temperature is 200℃~500℃.

[0025] Optionally, the inert gas includes one or more of nitrogen, argon and helium, and the reaction space velocity is 0.25h -1 ~6h -1 , carrier gas space velocity is 3000h -1 ~5000h -1 , the reaction temperature is 300℃~400℃.

[0026] Specifically, the present invention synthesizes for the first time a dendritic mesoporous silica catalyst loaded with transition metals, selects a dendritic mesoporous silica with a unique central radial pore structure as a carrier, which has a dendritic cavity structure, and further loads transition metals Zn and Zr on the dendritic mesoporous silica to achieve a high loading of transition metals; at the same time, the preparation process is simple and easy to industrialize, and has good application prospects in the ethanol to butadiene reaction, can achieve high activity, high selectivity, and high stability in the production of the target product butadiene from ethanol, and has significant advantages such as low cost and easy preparation.

[0027] Specifically, the catalyst provided by the present invention exhibits excellent performance in the one-step ethanol to butadiene reaction. It can maintain ultra-high stability in a wide temperature range. Its large specific surface area and suitable acidity ensure its high reaction conversion rate and selectivity, while its ultra-low carbon deposition rate ensures its excellent stability. More importantly, the catalyst exhibits an extremely low carbon deposition rate, which effectively prolongs the service life of the catalyst, providing strong support for the industrial application of ethanol to butadiene technology.

[0028] Implementing the embodiments of the present invention will have the following beneficial effects:

[0029] (1) The synthesis cycle of the carrier NMSS of the present invention is short, the process is relatively simple, and it is easy to prepare in large quantities. At the same time, the template agent used in the preparation process is cheaper than the template agents of other molecular sieves, and cheap and easily available Zn and Zr are selected as active components, so the industrialization cost is lower.

[0030] (2) The present invention utilizes Zn and Zr on the carrier NMSS to exhibit a significant synergistic effect, and the catalytic activity and butadiene selectivity are significantly better than those of other metal-supported catalyst systems, including AgZr / NMSS and CuZr / NMSS.

[0031] (3) Under the same Zn and Zr active component loading, the ZnZr / NMSS catalyst of the present invention can achieve the highest butadiene yield compared to other commonly used silicon-based carriers; and compared with the ZnZr-loaded catalysts reported in the literature, it has the lowest active component content, is inexpensive and easy to obtain, and has a low cost.

[0032] (4) The catalyst of the present invention has high reaction stability, far exceeding the highest stability of 80h reported so far, and can reach more than 200h.

[0033] (5) The preferred ZnZr / NMSS catalyst has high activity and butadiene selectivity in the one-step ethanol to butadiene reaction. Under the optimized reaction conditions, the butadiene selectivity is as high as more than 80%. Taking the above factors into consideration, the catalyst of the present invention has a good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 TEM and mapping images of 0.5% Zn2% Zr / NMSS of Example 2 of the present invention.

[0035] Figure 2 This is a graph showing the physical adsorption results of catalysts supported on different silicon-based carriers in Example 2 of the present invention and Comparative Example 3.

[0036] Figure 3 The catalysts supported by different silicon-based carriers in Example 2 and Comparative Example 3 of the present invention were heated at 350°C for 0.96 h. -1 Figure 2. Stability investigation results under reaction conditions.

[0037] Figure 4 The catalysts supported by different silicon-based carriers in Example 2 and Comparative Example 3 of the present invention were heated at 400°C for 0.96 h. -1 Figure 2. Stability investigation results under reaction conditions.

[0038] Figure 5 This is a graph showing the thermogravimetric characterization results of the stability test of catalysts supported on different silicon-based supports in Example 2 and Comparative Example 3 of the present invention.

[0039] Figure 6 This is a graph showing the carbon deposition rate results of catalysts supported on different silicon-based carriers after normalization treatment in Example 2 of the present invention and Comparative Example 3. DETAILED DESCRIPTION

[0040] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.

[0041] Example 1

[0042] The preparation method of the dendritic mesoporous silica of this embodiment comprises the following steps:

[0043] (1) 96 mL of 25 wt% hexadecyltrimethylammonium chloride (CTAC) was added to 144 mL of water and mixed, and then 0.72 g of triethanolamine (TEA) was added and mixed. The resulting solution was transferred to a 500 mL round-bottom flask and slowly stirred in an oil bath at 60° C. for 1 h to obtain an aqueous phase;

[0044] (2) 80 mL of tetraethyl orthosilicate / cyclohexane (20 vol / vol%) solution was added to the aqueous phase obtained above, and the mixture was stirred continuously for 12 h in an oil bath at 75 °C to completely remove the cyclohexane solution in the upper oil phase. The mixture was heated to 90 °C and stirred for aging for 3 h. After the reaction was completed, the mixture was washed by centrifugation several times and dried in an oven at 80 °C overnight. The mixture was then calcined at 650 °C in an air atmosphere for 4 h to obtain dendritic mesoporous silica (NMSS).

[0045] Example 2

[0046] Preparation of 0.5% ZnX% Zr / NMSS catalysts with different loading amounts:

[0047] Step a, dissolving zinc nitrate and zirconium oxynitrate in water, and impregnating the NMSS carrier obtained in Example 1 with equal volumes, the loading rate of Zn is 0.5%, and the loading amount of Zr is 1%, 2%, 4%, 8%, 16%, 20%, respectively, and drying at 100° C. for 8 h;

[0048] Step b, calcining the above samples at 550°C in a muffle furnace for 4 hours to obtain catalysts with different loading amounts, namely 0.5% Zn1% Zr / NMSS, 0.5% Zn2% Zr / NMSS, 0.5% Zn4% Zr / NMSS, 0.5% Zn8% Zr / NMSS, 0.5% Zn16% Zr / NMSS, and 0.5% Zn20% Zr / NMSS.

[0049] In Example 2, the TEM image and mapping image of 0.5% Zn2% Zr / NMSS are as follows: Figure 1 As shown in the figure, the catalyst is composed of small spheres of about 100 nm. The nanospheres have a dendritic mesoporous structure with a pore size of about 3 nm, which determines its high specific surface area. The mapping results show that Zn and Zr are highly dispersed on the NMSS carrier without particles.

[0050] Comparative Example 1

[0051] Preparation of Zn / NMSS catalysts with different loading amounts:

[0052] Step a, dissolving zinc nitrate in water, and impregnating the same volume with the NMSS carrier obtained in Example 1, with the Zn loading amount selected as 0.5%, 2%, 5%, 10%, 20%, respectively, and drying at 100° C. for 8 h;

[0053] Step b, calcining the above samples at 550° C. in a muffle furnace for 4 h to obtain catalysts with different loading amounts, namely 0.5% Zn / NMSS, 2% Zn / NMSS, 5% Zn / NMSS, 10% Zr / NMSS, and 20% Zr / NMSS.

[0054] Comparative Example 2

[0055] The catalysts of this comparative example are prepared from 0.5%Cu2%Zr / NMSS and 0.5%Ag2%Zr / NMSS respectively. The preparation process is the same as that of Example 2, except that zinc nitrate is replaced by copper nitrate and silver nitrate respectively.

[0056] Comparative Example 3

[0057] The catalysts in this comparative example are 0.5% Zn2% Zr / support catalysts loaded on different silicon-based carriers, and the carriers are hydrated SiO2, gas-phase SiO2, mesoporous SiO2, Silicate-1 and SBA-15, respectively. Among them, hydrated SiO2 and gas-phase SiO2 were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., mesoporous SiO2 was purchased from Qingdao Ocean Chemical Co., Ltd., and SBA-15 was purchased from Nankai Catalyst Factory. The above carriers were used directly after purchase without further treatment.

[0058] The synthesis process of Silicate-1 is as follows: tetrapropylammonium hydroxide (TPAOH) is used as a template, tetraethyl orthosilicate (TEOS) is used as a silicon source, and the molar ratio of the synthetic gel is SiO2:0.3TPAOH:30H2O. The resulting solution is stirred for 3 hours until TEOS is completely hydrolyzed, and then transferred to a stainless steel reactor lined with polytetrafluoroethylene and hydrothermally crystallized at 170°C for 3 days. The synthesized sample is centrifuged and washed, dried at 80°C, and calcined at 550°C for 4 hours to obtain the Silicate-1 sample.

[0059] Example 3

[0060] Evaluation process of catalyst for ethanol to butadiene: 0.25 g of the catalyst prepared in Example 2 and Comparative Examples 1-3 was pelletized and loaded into a fixed bed reactor, and the raw materials were brought into the reactor by pump feeding and nitrogen carrier gas (flow rate of 40 mL / min). The flow rate of ethanol was 0.005 mL / min, and the reaction space velocity was WHSV=0.96 h -1 , the reaction temperature is 350°C, and the test results of ethanol conversion rate, acetaldehyde selectivity and butadiene selectivity are shown in the following table.

[0061] Reaction conversion and selectivity calculation method:

[0062] Ethanol conversion rate (%) = (n 反应前的乙醇 -n 反应后剩余乙醇 ) / n 反应前的乙醇 *100%

[0063] Acetaldehyde conversion rate (%) = (n 反应前的乙醛 -n 反应后剩余乙醛 ) / n反应前的乙醛 *100%

[0064] Total conversion rate (%) = (n 反应前的乙醇和乙醛 -n 反应后剩余乙醇和乙醛 ) / n 反应前的乙醇和乙醛 *100%

[0065] Butadiene selectivity (%) = 2n 产物中丁二烯 / (n 反应前的乙醇和乙醛 -n 反应后剩余乙醇和乙醛 )*100%

[0066] Table 1 Catalyst performance evaluation results of Comparative Example 1

[0067] catalyst Ethanol conversion rate (%) Acetaldehyde selectivity (%) Butadiene selectivity (%) 0.5%Zn / NMSS 50 80 5 2%Zn / NMSS 60 68 10 5%Zn / NMSS 70 62 12 10%Zn / NMSS 78 57 15 20%Zn / NMSS 80 56 15

[0068] From the results in Table 1, it can be seen that only the main product of the Zn / NMSS catalyst at the dehydrogenation center is acetaldehyde. With the increase of Zn content, the selectivity of acetaldehyde gradually decreases, and the selectivity of the condensation product butadiene increases. In order to achieve a suitable alcohol-aldehyde ratio, 0.5% Zn is selected as the preferred loading amount.

[0069] Table 2 Catalyst performance evaluation results of Example 2 and Comparative Examples 2-3

[0070] catalyst Ethanol conversion rate (%) Butadiene selectivity (%) 0.5%Zn1%Zr / NMSS 70 55 0.5%Zn2%Zr / NMSS 75 80 0.5%Zn4%Zr / NMSS 77 75 0.5%Zn8%Zr / NMSS 78 70 0.5%Zn16%Zr / NMSS 80 60 0.5%Zn20%Zr / NMSS 85 50 0.5%Cu2%Zr / NMSS 90 35 0.5%Ag2%Zr / NMSS 63 58 <![CDATA[0.5% Zn 2% Zr / hydrated SiO2]]> 25 13 <![CDATA[0.5% Zn 2% Zr / Fumed SiO2]]> 55 42 <![CDATA[0.5% Zn 2% Zr / mesoporous SiO2]]> 44 37 0.5%Zn2%Zr / Silicate-1 56 8 0.5%Zn2%Zr / SBA-15 45 50

[0071] According to the results of Example 2, it can be seen that Example 2 has relatively good catalytic performance at a Zr content of 1% to 20%, among which the performance of 0.5% Zn2% Zr / NMSS is the most outstanding.

[0072] According to Example 2 and Comparative Example 2, Cu and Ag have poor synergistic effects with Zr, and the butadiene selectivity is low, while Zn and Zr have good synergistic effects, which can effectively promote the conversion of ethanol into butadiene.

[0073] According to Example 2 and Comparative Example 3, compared with other common microporous, mesoporous and macroporous silicon-based carriers hydrated SiO2, gas phase SiO2, mesoporous SiO2, Silicate-1 and SBA-15, the 0.5% Zn2% Zr / NMSS catalyst of Example 2 not only has a higher ethanol conversion rate, but also has an ultra-high butadiene selectivity of 80%, reflecting the superiority of the present invention.

[0074] Example 4

[0075] The difference between Example 4 and Example 3 is that the reaction temperature is changed. Except for the above differences, other operations are the same and will not be repeated here. The test results of ethanol conversion rate and butadiene selectivity of 0.5% Zn2% Zr / NMSS are shown in the following table.

[0076] Table 3 Performance evaluation results of 0.5% Zn2% Zr / NMSS catalyst at different reaction temperatures

[0077] Temperature(℃) Ethanol conversion rate (%) Butadiene selectivity (%) 250 1.1 0 275 5.2 8.2 300 14.9 31.2 325 38.6 52 350 75 80 375 97 75 400 100 70

[0078] It can be seen from Table 3 that 0.5% Zn2% Zr / NMSS can produce the target product butadiene under the reaction conditions of 275°C to 400°C, and the optimal reaction temperature is 350°C.

[0079] Example 5

[0080] The difference between Example 5 and Example 3 is that the different space velocities (WHSV) are changed. Except for the above differences, other operations are the same and will not be repeated here. The ethanol conversion rate and butadiene selectivity test results of 0.5% Zn2% Zr / NMSS are shown in the following table.

[0081] Table 4 Performance evaluation results of 0.5% Zn2% Zr / NMSS catalyst at different space velocities

[0082] <![CDATA[WHSV(h -1 )]]> Ethanol conversion rate (%) Butadiene selectivity (%) 0.38 100 82 0.96 75 80 1.92 50 60 3.84 40 45

[0083] It can be seen from Table 4 that 0.5% Zn2% Zr / NMSS can -1 ~3.84h -1 The target product butadiene was produced under the condition of space velocity, and the optimal space velocity of the reaction was 0.38h -1 , can achieve 100% conversion rate.

[0084] Example 6

[0085] The physical adsorption performance of 5% Zn2% Zr / NMSS and the catalyst in Comparative Example 3 was tested. The results are as follows: Figure 2 And as shown in Table 5.

[0086] Table 5 Physical adsorption results of 0.5% Zn2% Zr / support catalysts loaded on different silicon-based supports

[0087]

[0088] According to the results in Table 5, the catalyst 0.5% Zn2% Zr / NMSS has the largest specific surface area and is mostly mesoporous. Compared with other macroporous, mesoporous and microporous catalysts, the catalytic performance of 0.5% Zn2% Zr / NMSS in the embodiment of the present invention is the best. In addition, 0.5% Zn2% Zr / SBA-15 and 0.5% Zn2% Zr / mesoporous SiO2, which also have a relatively large specific surface and a mesoporous structure, have a far inferior catalytic effect to 0.5% Zn2% Zr / NMSS in the embodiment of the present invention, which may be due to their unique dendritic mesoporous structure.

[0089] Example 7

[0090] The stability of the 0.5% Zn2% Zr / NMSS catalyst and the catalyst in Comparative Example 3 were evaluated. The reaction conditions were the same as those in Example 3. The performance results are shown in FIG. Figure 3 As shown. Figure 3 It can be seen that at 350℃, WHSV=0.96h -1 Under the conditions, the 0.5% Zn2% Zr / NMSS catalyst can achieve an ultra-long stability of 172 hours, while the other catalysts not only have poor performance, but also have a significant decrease in stability within 30 hours.

[0091] Example 8

[0092] The stability of the 0.5% Zn2% Zr / NMSS catalyst and the catalyst in Comparative Example 3 was evaluated at high temperature, with the initial conversion rate reaching 100%, the reaction temperature being 400°C, and the other reaction conditions being the same as those in Example 3. The results are shown in FIG. Figure 4 As shown in Figure 4, at 400°C, WHSV = 0.96h -1 Under the conditions, the 0.5% Zn2% Zr / NMSS catalyst can still achieve stability of more than 120 hours, while the other catalysts are obviously deactivated within a few hours. This shows that under relatively harsh conditions, the 0.5% Zn2% Zr / NMSS catalyst can still maintain good reaction stability while maintaining high activity selectivity, reflecting the uniqueness and superiority of the present invention.

[0093] Figure 5 This is the thermogravimetric characterization diagram of the catalyst after stability test. Figure 6 The normalized carbon deposition rate of the catalyst is shown in Figure 2. As can be seen from the figure, the 0.5% Zn2% Zr / NMSS catalyst has the lowest carbon deposition rate, which determines its ultra-high reaction stability. The carbon deposition rates of the other catalysts are significantly higher than those of 0.5% Zn2% Zr / NMSS, so they deactivate faster in the same reaction time.

[0094] In summary, the mesoporous NMSS-loaded ZnZr catalyst provided by the present invention is applied to the one-step process for preparing butadiene from ethanol, and not only has the advantages of high conversion rate and high butadiene selectivity, but more importantly, its reaction stability far exceeds that of the currently reported catalysts, which can be attributed to its ultra-high specific surface area and low carbon deposition rate. In addition, the preparation process of the catalyst is simple, the cost is low, and it is easy to mass produce, laying a foundation for industrial application.

[0095] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A dendritic mesoporous silica supported catalyst, characterized in that: The catalyst comprises a dendritic mesoporous silica carrier and a transition metal supported on the dendritic mesoporous silica carrier; The transition metals are Zn and Zr.

2. The dendritic mesoporous silica supported catalyst according to claim 1, characterized in that: In the catalyst, the mass of Zn accounts for 0.5wt% to 20wt% of the total mass of the catalyst, and the mass of Zr accounts for 1wt% to 25wt% of the total mass of the catalyst.

3. The dendritic mesoporous silica-supported catalyst according to claim 1, characterized in that: The dendritic mesoporous silica carrier is a mesoporous SiO2 nanosphere with a dendritic skeleton structure. The diameter of the dendritic structure is 4nm-10nm, the diameter of the SiO2 nanosphere is 20nm-200nm, the pore size of the mesopore is 2nm-30nm, and the specific surface area is 400m 2 / g~700m 2 / g.

4. A method for preparing a dendritic mesoporous silica-supported catalyst as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: The soluble salt solution of the transition metal is co-impregnated into the dendritic mesoporous silica carrier, dried at 60°C to 200°C, and then calcined in an air atmosphere at a calcination temperature of 350°C to 750°C for 2h to 8h to obtain the dendritic mesoporous silica supported catalyst.

5. The preparation method according to claim 4, characterized in that: The calcination temperature is 500° C. to 700° C., and the calcination time is 2 h to 6 h.

6. The preparation method according to claim 4, characterized in that: The preparation method of the dendritic mesoporous silica carrier comprises the following steps: (1) adding a template to water and mixing to form a solution with a mass fraction of 5% to 35%, and then adding a catalyst and mixing to obtain an aqueous phase; (2) mixing the silicon source and the solvent to form an oil phase with a volume fraction of 5% to 40%; (3) stirring the oil phase and the water phase at 60°C to 90°C for 8h to 20h, removing the upper oil phase, and then heating to 80°C to 110°C and stirring and aging for 2h to 4h. After the reaction is completed, centrifugally washing and drying are performed, and then calcining at 300°C to 800°C in an air atmosphere for 1h to 8h to obtain the dendritic mesoporous silica carrier.

7. The preparation method according to claim 6, characterized in that: In step (1), the mixing temperature is 45° C. to 80° C., and the mixing time is 0.5 h to 2 h; the mass ratio of the template agent to the catalyst is 1:(100 to 500); the template agent is hexadecyltrimethylammonium chloride; and the catalyst is triethanolamine; In step (2), the molar ratio of the silicon source to the template is (0.5-1.5):1; the silicon source is tetraethyl orthosilicate; and the solvent is cyclohexane; In step (3), the drying temperature is 60°C to 120°C; the roasting temperature is 500°C to 700°C, and the roasting time is 2h to 6h.

8. Use of the dendritic mesoporous silica supported catalyst as claimed in any one of claims 1 to 3 in the reaction of ethanol to butadiene.

9. The use according to claim 8, characterized in that: The application includes: the reaction is carried out in a fixed bed reactor at normal pressure, and the reaction space velocity is 0.12h -1 ~10h -1 , using inert gas as carrier gas, the carrier gas space velocity is 500h -1 ~10000h -1 , the reaction temperature is 200℃~500℃.

10. The use according to claim 9, characterized in that: The inert gas includes one or more of nitrogen, argon and helium, and the reaction space velocity is 0.25h -1 ~6h -1 , carrier gas space velocity is 3000h -1 ~5000h -1 , the reaction temperature is 300℃~400℃.

Citation Information

Patent Citations

  • Solid catalyst for synthesizing butadiene from alcohol, and preparation and application thereof

    CN106861752A

  • Synthesis method of 1,3-butadiene and preparation method of catalyst

    CN109894144A

  • Nanometer pesticide preparation with dendritic mesoporous silica as carrier and preparation method and application thereof

    CN115968871A

  • Cu-Zr / SiO2 catalyst, preparation method thereof and application of Cu-Zr / SiO2 catalyst in one-step preparation of butadiene from ethanol

    CN116196924A

  • Carbon-modified Zr-based mesoporous SiO2 nanosphere catalyst as well as preparation method and application thereof

    CN116474756A